Survey Study for Causative Agents of Meningitis Patient in Babylon Province - Zaytoon A. Al-Khafaji; Safaa A.AL-Isawi; Zainab H. Al-zubaidy; Ameer Kadhim Al-Humairi (Indian Journal of Forensic Medicine & Toxicology, 2021)
One of the most dangerous infections that cause elevated morbidity and mortality rates is meningitis.Meningitis in children is one of the life threatening condition in pediatric age group, which needs properand early diagnosis in the emergency department. According to findings and clinical diagnosis (35.3%cases)considered bacterial while (64.7% cases) considered non bacterial meningitis. Most rate of infection ofmeningitis occurred in 2017 ( 38.3%),Male sex, Age< 1 year with a higher prevalence of meningitis. Weconcluded that Bacterial meningitis are still occupying large percentage of cases admitted to hospital, and ifun-diagnosed promptly will have a high mortality.